The stability of small curving arcs according to the theory of elasticity and creep - Bartaševičius, Algimantas (Lietuvos matematikos rinkinys, 1997)
There are solved the deformation and stability small curving arcs according to the theory of elasticity and creep. This solution shows that arcs bend v(t) increases and the arc equilibrium is not stable.